2020
DOI: 10.1002/stem.3189
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA mediates stroke-induced neurogenesis

Abstract: Neurogenesis contributes to poststroke recovery. Long noncoding RNAs (lncRNAs) participate in the regulation of stem cell self-renewal and differentiation. However, the role of lncRNAs in stroke-induced neurogenesis remains unknown. In this study, we found that H19 was the most highly upregulated lncRNA in neural stem cells (NSCs) of the subventricular zone (SVZ) of rats subjected to focal cerebral ischemia.Deletion of H19 suppressed cell proliferation, promoted cell death, and blocked NSC

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 61 publications
0
30
0
Order By: Relevance
“…The lncRNA MALAT-1 has been shown to have neuroprotective effects on spinal cord ischemic/reperfusion injury by regulating miR-204 (Qiao et al, 2018). LncRNAs have also been reported to participate in the regulation of stem cell self-renewal and differentiation in stroke-induced neurogenesis (Fan et al, 2020). Recent studies suggest that lncRNAs are important regulators of the pathophysiological processes of CNS diseases, especially those associated with ischemia; therefore, we are interested in the contribution of lncRNAs to endogenous neurological repair after CCSCI.…”
Section: Introductionmentioning
confidence: 99%
“…The lncRNA MALAT-1 has been shown to have neuroprotective effects on spinal cord ischemic/reperfusion injury by regulating miR-204 (Qiao et al, 2018). LncRNAs have also been reported to participate in the regulation of stem cell self-renewal and differentiation in stroke-induced neurogenesis (Fan et al, 2020). Recent studies suggest that lncRNAs are important regulators of the pathophysiological processes of CNS diseases, especially those associated with ischemia; therefore, we are interested in the contribution of lncRNAs to endogenous neurological repair after CCSCI.…”
Section: Introductionmentioning
confidence: 99%
“…Also, H19 was shown to modulate miRNAs associated with neurogenesis. Notably, functional rehabilitation following stroke was retarded when H19 was blocked in NSCs (Fan et al, 2020). In another investigation, the sensorimotor cortex displayed upregulation of lncRNA H19 expression after MCAO.…”
Section: Lncrnas As Putative Biomarkers and Therapeutic Targetsmentioning
confidence: 95%
“…lncRNA H19 has also been shown to make a significant contribution to stroke pathology. In NSCs isolated from the SVZ of rats afflicted with focal cerebral ischemia, H19 lncRNA expression was significantly increased (Fan et al, 2020). H19 knockdown hindered NSC proliferation and differentiation, along with spurring cell death.…”
Section: Lncrnas As Putative Biomarkers and Therapeutic Targetsmentioning
confidence: 97%
“…Using ChIRP-Western blot and RNA immnunoprecipitation (RIP) assay, chromatin proteins including SUZ12, EZH2 and H3K27me3 were observed to be physically associated with long non-coding RNA (lncRNA) H19, whose association was significantly higher in the ischemic NSCs compared with those from non-ischemic NSCs. Furthermore, our data demonstrate that knockdown of lncRNA markedly reduced levels of EZH2 and H3K27me3 at the promoters of cell cycle-related genes, leading to the upregulation of p27 expression and consequently inhibition of NSC proliferation [ 80 ]. Our novel preliminary data suggest that stroke alters histone factors and thereby the recruitment of epigenetic states to target genes, which underlie stroke-induced neurogenesis.…”
Section: Epigenetics In Adult Neurogenesis After Strokementioning
confidence: 99%
“…In total, 409 mRNAs were identified to be significantly upregulated and 255 were downregulated in ischemic NSCs compared with non-ischemic NSCs. Our study for the first time revealed differential lncRNA profiles and lncRNA–mRNA co-expression network in the NSCs that are associated with stroke-induced neurogenesis [ 80 ]. Furthermore, we demonstrated that the top upregulated lncRNA H19 mediates the proliferation and neuronal differentiation of NSCs by recruiting chromatin remodeling proteins and by regulating miR-675 expression to modulate neurogenesis-related transcription.…”
Section: Epigenetics In Adult Neurogenesis After Strokementioning
confidence: 99%